Predicables and theory of Definitions related to Fakhr-Al-Din Al-Razi - Razouk, Ebraheem; Aljazr, Hana; Naseef, Nebal (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research tries to concentrate on an essential and important issue in ancient logic which is the issue of predicable and the theory of definition related to Fakhr-Al-Din Al-Razi . in this search we will discuss the issue of predicables and the relationship between them by Fakhr-Al-Din Al-Razi. And we will try to show their role in the possibility of being the theory of definition and we will show if Fakhr-Al-Din Al-Razi refered to the eral definition influenced by Aristotle , or nominal definition influenced by stoicism, and if the definition refers to Quiddity or it is only refers to the properties of this thing , and we will try to explain his point of view of predicables and if they have an existence outside or they are only names havn,t any existence outside minds.